2022
DOI: 10.26434/chemrxiv-2022-kxcg8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent Mechanistic Pathways for Copper(I) Hydrophosphination Catalysis: Understanding that Allows for Diastereoselective Hydrophosphination of a Tri-substituted Styrene

Abstract: Readily available and bench-stable Cu(acac)2 (1) addresses many challenges in exploratory hydrophosphination catalysis. Mechanistic investigations were performed to answer questions that remain about the reactivity of 1, the role of light in the catalysis, and to provide direction for further study. A divergent Hammett plot indicates differing mechanisms based on electron density at the alkene substrate. A radical process was eliminated based on trapping reactions and in-situ EPR experiments. Isotopic labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In this instance, Liptrot's compound, (NHC)CuPPh 2 , 97 was both highly active for photocatalytic hydrophosphination and already structurally characterized. 98 Computational analysis of this compound showed that the LUMO has significant Cu–P anti-bonding character. Like zirconium, it was hypothesized that photoexcitation from the HOMO, which has high P lone pair character, weakens the Cu–P bond, facilitating insertion.…”
Section: Metal–phosphido Bondsmentioning
confidence: 96%
“…In this instance, Liptrot's compound, (NHC)CuPPh 2 , 97 was both highly active for photocatalytic hydrophosphination and already structurally characterized. 98 Computational analysis of this compound showed that the LUMO has significant Cu–P anti-bonding character. Like zirconium, it was hypothesized that photoexcitation from the HOMO, which has high P lone pair character, weakens the Cu–P bond, facilitating insertion.…”
Section: Metal–phosphido Bondsmentioning
confidence: 96%